Uncovering the wider impact of COVID-19 public health measures on the lives of children with complex care needs and their families in the Canadian Maritimes: a qualitative study - Janet A Curran; Christine Cassidy; Helen Wong; Catie Johnson; Holly McCulloch; Mary-Ann Standing; Julie Clegg; Jessie-Lee McIsaac; Jennifer Lane; Robyn Kydd; Lisa Keeping-Burke; De-Lawrence Lamptey; et al. (BMJ Paediatrics Open)
Introduction The COVID-19 pandemic resulted in rapid change across all sectors, including healthcare and education, as necessary public health measures (PHM) were implemented to protect the public. Children with complex care needs (CCCN) use health and specialised education services at a higher rate than the general paediatric population and were disproportionately affected by these changes. The current study aimed to explore the wider impacts of COVID-19 PHM on CCCN and their families in the Maritime provinces of Canada.Methods Semi-structured interviews were conducted from March to September 2023, with CCCN aged 15–17 years old and caregivers of CCCN. Interviews were coded by two independent reviewers using the Ten Domains of Health Framework and interpreted using a phenomenological approach.Results 21 parents and 3 youth from across the three Maritime provinces participated in the interviews. Key themes that emerged from the interviews included families carrying the burden of stress and fear, creating and protecting safe spaces, living through uncertainty, accumulating consequences of PHM and feeling disconnected. Within these themes, families mostly described negative impacts, although some positive experiences were also described.Conclusion The findings of the current study will assist in the co-development of recommendations for healthcare and education decision-makers to reduce the negative impacts of future public health emergencies.